Early and Late-Phase 24 h Responses of Stored Red Blood Cells to Recipient-Mimicking Conditions - Tzounakas, Vassilis L.; Anastasiadi, Alkmini T.; Karadimas, Dimitrios G.; Velentzas, Athanassios D.; Anastasopoulou, Violetta I.; Papageorgiou, Effie G.; Stamoulis, Konstantinos; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Antonelou, Marianna H. (Frontiers in Physiology, 2022)
The 24-hour (24h) post-transfusion survival of donor red blood cells (RBCs) is an important marker of transfusion efficacy. Nonetheless, within that period, donated RBCs may encounter challenges able to evoke rapid stress-responses. The aim of the present study was to assess the effect of exposure to plasma and body temperature upon stored RBCs under recipient-mimicking conditions in vitro from the first hours “post-transfusion” up to 24h. For this purpose, packed RBCs from seven leukoreduced CPD/SAGM units were reconstituted with plasma of twenty-seven healthy individuals and incubated for 24h at 37oC. Three units were additionally used to examine stress-responses in 3-hour intervals post mixing with plasma (N=5) until 24h. All experiments were performed in young, middle-aged, and old stored RBCs. Hemolysis, redox, morphology, membrane protein binding and vesiculation parameters were assessed. Even though spontaneous hemolysis was minimal post-reconstitution, it presented a time-dependent increase. A similar time-course profile was evident for the concentration of procoagulant extracellular vesicles and the osmotic fragility (younger RBCs). On the contrary, mechanical fragility and reactive oxygen species accumulation were characterized by increases in middle-aged RBCs, evident even from the first hours in the recipient-mimicking environment. Finally, exposure to plasma resulted in rapid improvement of morphology, especially in middle-aged RBCs. Overall, some RBC properties vary significantly during the first 24h post-mixing, at levels different from both the storage ones and the standard end-of-24h. Such findings may be useful for understanding the performance of RBCs and their possible clinical effects −especially on susceptible recipients− during the first hours post-transfusion.